Customer’s Repurchase Decision of Fruits and Vegetables Through E-Commerce Sites during Omicron Outbreak in Surabaya - Sekarnurani, Dinda Ayu; Jamhari, Jamhari; Utami, Arini Wahyu (Agro Ekonomi, 2023)
In the past few years, the number of e-commerce businesses in Indonesia is increasing including those that offer vegetables and fruits. Due to COVID-19 outbreak, transactions through e-commerce sites had also increased. During the outbreak, customers in Indonesia had a tendency to allocate their income for essential needs such as vegetables and fruits. This study aims to: (1) assess the frequency of vegetables and fruits purchases through e-commerce sites before the Omicron outbreak (October – December 2021) and during the Omicron outbreak (January – March 2022); and (2) examine the determinant factors of customers repurchase decision to buy vegetables and fruits through e-commerce sites. Data were collected using online questionnaire distributed to 140 respondents that were selected based on age and experience of purchasing vegetables and fruits online. The differences in frequency of purchasing vegetables and fruits through e-commerce sites before and during the Omicron outbreak were analyzed using the Wilcoxon test. Meanwhile, the determinant factors of the decision to repurchase vegetables and fruits through e-commerce sites were analyzed using binary logistic regression. The results showed that there is no significant difference in frequencies between purchasing before and during the Omicron outbreak. Education, products, price discounts, promotions, and COVID-19 situation are the determinant factors of repurchase decision of vegetables and fruits through e-commerce sites.  As the writer conducting this study, there was no previous study on the same case that using the combination of demographic, marketing mix, and situational factor as determinant factors on customers repurchase decision through online platforms.